E-learning: a study of readiness and social environment factors rural student of studying design and technology subjects - Nuid, Mohd Sarizan; Jamaluddin, Rahimah; Abd Wahab, Nabila (IJ Publication, 2023)
The implementation of online learning has its advantages and disadvantages. Online learning is proven by implementing this method during the Covid-19 Pandemic that hit the country from 2020 to 2021. However, this learning method is suitable to continue to be used to overcome the problem of students dropping out of school due to the need for public transport. This paper aims to examine the willingness of rural students to follow online learning and the social environment factors of rural students in studying Design and Technology subjects. The study was conducted in Keningau, Sabah. Involving 207 junior high school students at Sook National High School. The sample selection was made randomly from first, second and third-grade students. The instrument used is an adaptation of the study of Siti Nurbaizura and Nurfaradilla (2020). The study's findings show that students' willingness to follow online learning is high, with a mean value of 3.88 (SP=0.70). The social environment factor recorded a relatively high value for all the six factors studied, which was 3.02 (SP=0.48). Findings show that the social anxiety factor regarding parental support, knowledge and skills about technology and two-way communication between students and teachers recorded a mean value of more than 3.92. The implementation of online learning can be continued for in-depth students by holding hybrid learning sessions. This action can overcome the problem of students dropping out of school due to the need for public transport and other factors.